2020
DOI: 10.1111/ejn.14966
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological priming effects confirm that the extrastriate symmetry network is not gated by luminance polarity

Abstract: Here we consider reflectional (mirror) symmetry only, although it not the only type (Mach, 1886). In reflectional symmetry, there is a correlation between element position on either side of the axis (Barlow & Reeves, 1979). Therefore models of symmetry perception consider how local element position signals are integrated to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…In other recently published work, we found SPN priming transferred between black and white reflections. This shows the regularity code is independent of luminance polarity [36] as anticipated by previous work using other methods [37][38][39]. It seems that different regularities are coded by overlapping neural populations, but only when they are presented at the same retinal location.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…In other recently published work, we found SPN priming transferred between black and white reflections. This shows the regularity code is independent of luminance polarity [36] as anticipated by previous work using other methods [37][38][39]. It seems that different regularities are coded by overlapping neural populations, but only when they are presented at the same retinal location.…”
Section: Plos Onesupporting
confidence: 82%
“…As mentioned, Makin et al [ 36 ] used SPN priming technique to demonstrate that the regularity code is luminance independent. Future work could use the SPN priming effect to answer other questions about symmetry coding.…”
Section: Discussionmentioning
confidence: 99%
“…The repetition of identical information along the central axis may have caused an enhancement (priming) effect on the ERP response in t2. Recent research has shown that repeated presentations of symmetrical patterns increase SPN amplitude 43,86,87 ; this effect has been termed SPN priming 86 . This response enhancement, however, is greater when the second exemplar is different from the rst one 43 .…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…The repetition of identical information along the central axis may have caused an enhancement ( priming ) effect on the ERP response in t2. Recent research has shown that when three symmetrical images are presented in succession, SPN amplitude increases 43 , 86 , 87 . This effect has been termed SPN priming 87 , and suggests that amplitude of the extra-striate symmetry response is partially determined by the immediately preceding stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid confusion, we should mention a phenomenon called SPN priming (i.e. increase in SPN amplitude with presentation of symmetrical images in succession 86 88 ). This form of past-history effect reflects interdependency of responses to fully-visible image symmetries.…”
Section: Introductionmentioning
confidence: 99%